Frontiers of Remote Sensing Information Processing 2003
DOI: 10.1142/9789812796752_0003
|View full text |Cite
|
Sign up to set email alerts
|

Scene Modeling and Image Mining With a Visual Grammar

Abstract: Automatic content extraction, classification and content-based retrieval are highly desired goals in intelligent remote sensing databases. Pixel level processing has been the common choice for both academic and commercial systems. We extend the modeling of remotely sensed imagery to three levels: Pixel level, region level and scene level. Pixel level features are generated using unsupervised clustering of spectral values, texture features and ancillary data like digital elevation models. Region level features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In previous work [25], we used an automatic segmentation algorithm that breaks an image into many small regions and merges them by minimizing an energy functional that trades off the similarity of regions against the length of their shared boundaries. We have also recently experimented with several segmentation algorithms from the computer vision literature.…”
Section: Region Segmentationmentioning
confidence: 99%
“…In previous work [25], we used an automatic segmentation algorithm that breaks an image into many small regions and merges them by minimizing an energy functional that trades off the similarity of regions against the length of their shared boundaries. We have also recently experimented with several segmentation algorithms from the computer vision literature.…”
Section: Region Segmentationmentioning
confidence: 99%
“…In previous work [8], we used an automatic segmentation algorithm based on energy minimization, and used k-means and Gaussian mixture-based clustering algorithms to group and label the resulting regions according to their features. Our newer experiments showed that some popular density-based and graphtheoretic segmentation algorithms were not successful on our data sets because of the large amount of data and the detailed structure in multi-spectral images.…”
Section: Scene Decompositionmentioning
confidence: 99%
“…These computations can be significantly simplified by applying a coarse-to-fine search to find region pairs that have a potential overlap or are very close to each other. In previous work [8,9], we used brute force comparisons of region pairs within smaller tiles obtained by dividing the original scene into manageable sized images. However, regions that occupy multiple tiles may not be handled correctly after that division.…”
Section: Pairwise Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations